2023
DOI: 10.12688/f1000research.129873.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and attitude towards Stroke among the UAE population during the COVID-19 pandemic: A cross-sectional study

Azza Ramadan,
Zelal Kharaba,
Rose Ghemrawi
et al.

Abstract: Background: Despite significant advancements in healthcare, the burden of stroke continues to rise in the developed world, especially during the COVID-19 pandemic. Association between COVID-19 infection and stroke is well established. Factors identified for the delay in presentation and management include a lack of awareness regarding stroke. We aimed to assess the general public knowledge and attitudes on stroke and stroke risk factors in the United Arab Emirates during the COVID-19 pandemic. Methods: A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…Our results revealed a significant correlation between gender and knowledge about stroke risk factors, as females had better knowledge compared to males. In agreement with our study findings, other studies reported similar results ( 32–35 ). On the other hand, better knowledge of stroke warning signs among males was reported as well ( 8 , 27 ).…”
Section: Discussionsupporting
confidence: 94%
“…Our results revealed a significant correlation between gender and knowledge about stroke risk factors, as females had better knowledge compared to males. In agreement with our study findings, other studies reported similar results ( 32–35 ). On the other hand, better knowledge of stroke warning signs among males was reported as well ( 8 , 27 ).…”
Section: Discussionsupporting
confidence: 94%